Administrative Resilience in Middle Eastern Healthcare within Conflict Zones - Agustina Bangun,; M. Agung Rahmadi,; Luthfiah Mawar,; Suranta Ginting,; Hariana Erdewi Sinaga,; Helsa Nasution,; Nurzahara Sihombing, (International Journal Of Health Science, 2025)
This study examines the construct of administrative resilience within mental and physical health service systems in Middle East conflict zones using Confirmatory Factor Analysis (CFA) within Structural Equation Modeling (SEM). Data were derived from 847 policy documents and operational reports from twelve countries (2018–2024), accessed through official online sources. The measurement model showed good fit indices (χ²/df = 2.134, CFI = 0.962, TLI = 0.955, RMSEA = 0.047, SRMR = 0.038), indicating structural stability and validity of the theoretical model. CFA confirmed four dimensions of administrative resilience with significant loadings: Adaptive Policy (λ = 0.871, CR = 12.453, p < 0.001), Cross-Sector Coordination (λ = 0.834, CR = 11.287, p < 0.001), Professional Competence (λ = 0.792, CR = 10.564, p < 0.001), and Operational Stability (λ = 0.815, CR = 11.098, p < 0.001). Reliability results were strong (Cronbach's α = 0.863–0.921; Composite Reliability = 0.879–0.934; AVE = 0.647–0.782). Findings reinforce Boin and Lodge’s (2016) concept of organizational resilience and extend Comfort et al. (2010) by integrating operational stability as a relevant dimension in conflict settings. Unlike Kruk et al. (2015), which focused on general health systems, this study identifies unique adaptive mechanisms within dual mental–physical services while addressing the fragmentation gap noted by Jawad et al. (2019) through empirical formulation of interdependent administrative dimensions.